Electrophotographic conductive member, process cartridge, and electrophotographic image forming device
The electrophotographic conductive member with a matrix-domain structure and specific impedance and volume resistivity characteristics addresses the issue of image defects caused by reduced charging bias, ensuring high-quality image formation.
Patent Information
- Application Number
- JP2024153704
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-09-06
- Publication Date
- 2025-04-09
AI Technical Summary
When reducing the charging bias in electrophotographic image forming devices, the developer is transferred to non-exposed portions of the photoreceptor, leading to image defects such as 'cover' or 'inversion fog'.
An electrophotographic conductive member with a conductive layer having a matrix-domain structure, where the domains contain crosslinked second rubber and conductive particles, and are exposed on the outer surface. The conductive member is designed to have specific impedance and volume resistivity characteristics to prevent uneven discharges and ensure efficient charge transfer.
The proposed solution effectively prevents the occurrence of 'cover' and 'inversion fog' even at low charging biases, enabling the formation of high-quality electrophotographic images.
Smart Images

Figure 2025058940000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrophotographic conductive member, a process cartridge, and an electrophotographic image forming apparatus. [Background technology]
[0002] The electrophotographic image forming apparatus has a charging member, a transfer member, and a developing member. The charging member is a member that generates a discharge between itself and an electrophotographic photoreceptor to charge the surface of the electrophotographic photoreceptor. The developing member is a member that controls the charge of the developer coated on its surface by frictional charging, gives a uniform charge amount distribution, and uniformly transfers the developer to the surface of the electrophotographic photoreceptor according to an applied electric field. The transfer member is a member that transfers the developer from the electrophotographic photoreceptor to a print medium such as paper or an intermediate transfer member, and at the same time generates a discharge to stabilize the developer after transfer. In the electrophotographic image forming process, the surface of a photoreceptor is charged, and then the charged surface of the photoreceptor is exposed to light to form a latent image. A developing member transfers developer to the latent image on the photoreceptor surface, and the image is then transferred to a paper medium by a transfer member.
[0003] In recent years, in response to demands for energy saving in electrophotographic image forming apparatuses, it has been considered to reduce the voltage applied to conductive members such as a charging member, a developing member, and a transfer member. For example, by reducing the voltage applied between the charging member and the photosensitive member, which is the member to be charged (hereinafter also referred to as the "charging bias"), the voltage applied to the developing member and the transfer member can also be reduced, making it possible to reduce energy consumption in an electrophotographic image forming apparatus. Patent Document 1 discloses a charging member capable of suppressing the occurrence of fogging on an electrophotographic image. In the charging member, the conductive layer has a matrix-domain structure in which domains containing a crosslinked product of a second rubber and conductive particles are dispersed in a matrix containing a crosslinked product of a first rubber. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-166209 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present inventors, when forming an electrophotographic image using the charging member according to Patent Document 1, attempted to set the charging bias applied between the charging member and the electrophotographic photosensitive member to a voltage (e.g., -700V to -900V, more specifically, -800V) lower than a general charging bias (e.g., -1300V). As a result, when the charging bias was lowered, the developer was transferred to the non-exposed portion of the surface of the photosensitive member to which the developer was not originally transferred, and as a result, so-called "fogging" was sometimes generated in the electrophotographic image.
[0006] In at least one embodiment of the present disclosure, the charging bias is, for example, −700 V to −900 V. The present disclosure is directed to providing an electrophotographic conductive member capable of preventing the occurrence of fogging on an electrophotographic image even when a low charging bias such as that described above is applied. At least one aspect of the present disclosure is also directed to providing a process cartridge contributing to the formation of high-quality electrophotographic images. At least one aspect of the present disclosure is also directed to providing an electrophotographic image forming apparatus capable of forming high-quality electrophotographic images. [Means for solving the problem]
[0007] According to at least one aspect of the present disclosure, a support having an electrically conductive outer surface; a conductive layer disposed on an outer surface of the support, the conductive layer has a matrix containing a crosslinked product of a first rubber and a plurality of domains dispersed in the matrix, the plurality of domains include a crosslinked product of a second rubber and conductive particles; at least a portion of the plurality of domains are exposed at an exterior surface of the electrophotographic conductive member; the outer surface of the electrophotographic conductive member is composed of the matrix and an exposed portion of the domain exposed on the outer surface of the electrophotographic conductive member, An electrode is provided directly on the outer surface of the electrophotographic conductive member, and an AC voltage having an amplitude of 1 V and a frequency of 1.0 Hz is applied between the outer surface of the support and the electrode in an environment of a temperature of 23° C. and a relative humidity of 50%. The impedance is 1.0×10 3 ~1.0×10 8 Ω, the domain exposed on the outer surface of the electrophotographic conductive member is designated as domain A, and in a cross section of the domain A in the thickness direction of the conductive layer, the maximum length of the domain A in the thickness direction of the conductive layer is designated as Ld, A region having a thickness of 0.1×Ld on the farthest side from the support in the cross section of the domain A is defined as a first region, When a region having a thickness of 0.1×Ld on the side closest to the support in the cross section of the domain A is defined as a second region, a volume resistivity R1 of a portion of the first region that is not the conductive particles and a volume resistivity R2 of a portion of the second region that is not the conductive particles satisfy R1>R2; Electrophotographic conductive materials is provided.
[0008] According to at least one aspect of the present disclosure, there is provided a process cartridge configured to be detachably attachable to a main body of an electrophotographic image forming apparatus, the process cartridge including the electrophotographic conductive member of the present disclosure. In accordance with at least one aspect of the present disclosure, there is provided an electrophotographic imaging apparatus comprising an electrophotographic conductive member of the present disclosure. Effect of the Invention
[0009] According to at least one aspect of the present disclosure, an electrophotographic conductive member that contributes to preventing the occurrence of fogging on an electrophotographic image when a charging bias is low can be obtained. Also, according to at least one aspect of the present disclosure, a process cartridge that can stably form a high-quality electrophotographic image can be obtained. Furthermore, according to at least one aspect of the present disclosure, an electrophotographic image forming apparatus that can stably form a high-quality electrophotographic image can be obtained. [Brief description of the drawings]
[0010] [Figure 1] Schematic cross-sectional view of a conductive roller according to one embodiment of the present disclosure. [Diagram 2] Schematic cross-sectional view of a process cartridge [Diagram 3] Schematic diagram of an electrophotographic image forming apparatus [Figure 4] Impedance measurement diagram [Diagram 5] FIG. 1 is an enlarged cross-sectional view of a surface of a conductive layer of a conductive roller according to an embodiment of the present disclosure; [Figure 6] FIG. 1 is an explanatory diagram of a domain at least part of which is exposed to the outer surface of a conductive layer of a conductive roller according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In this specification, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower and upper limits which are the endpoints, unless otherwise specified. In addition, when a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In the present disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.
[0012] The present inventors have investigated the cause of fog that occurs in an electrophotographic image when the charging member according to Patent Document 1 is applied with a low charging bias. First, the mechanism by which fogging occurs will be described. Note that here, the magnitude (high / low) of the potential of the surface of the photoconductor and the potential of the charging bias and the like refers to the magnitude (high / low) when compared in absolute value. In the electrophotographic image forming process, a charging bias is applied to a charging member to charge the surface of a photoconductor, and then the charged surface of the photoconductor is exposed to light to draw an electrostatic latent image. Next, a voltage (developing bias) is applied to a developing member carrying a developer. Then, due to the potential difference between the electrostatic latent image portion of the surface of the photoconductor and the surface of the developing member, the developer charged to the normal polarity (negative) is transferred to the electrostatic latent image on the surface of the photoconductor. At this time, the potential difference between the surface of the photoconductor in the non-exposed area and the surface of the developing member is called Vback. The value of Vback is closely correlated with the value of fog. When Vback is small, the electric field for retaining the developer on the developing member side is weakened, and fog (ground fog) tends to increase. On the other hand, when Vback is large, developer of the opposite polarity (positive) transfers to the surface of the photoconductor, and fog (reverse fog) tends to increase. The developer of the opposite polarity that has been transferred to the photoconductor surface due to the reversal fogging is not easily transferred to the printing medium or the intermediate transfer body surface, which are set to a lower potential than the photoconductor surface in the exposed area. Therefore, although the effect on the image is small, the consumption of the developer may increase.
[0013] In the course of their investigation, the present inventors focused on the conductive domains exposed on the outer surface of the charging member according to Patent Document 1. In the charging member according to Patent Document 1, electrons are transferred between a plurality of domains in sequence from the conductive support side of the elastic layer to the outer surface side of the elastic layer, and it is believed that ultimately, discharge occurs from the domains exposed on the surface of the charging member toward the electrophotographic photoreceptor. A non-conductive matrix exists between the domains inside the elastic layer, but the outer surface of the elastic layer is exposed to domains with low volume resistivity, which makes it easy for fine discharge unevenness to occur. As a result, it was inferred that fine potential unevenness occurs on the surface of the photoreceptor. When the charging bias is low, the difference in surface potential between the exposed and non-exposed parts of the photoreceptor becomes small, and as a result, the setting range of the development bias is also narrowed. Therefore, there is a tendency to lower the development bias and increase Vback in order to prioritize the reduction of background fog, which is likely to cause image defects. It is inferred that as a result of increasing Vback, the inversion fog increases even with fine surface potential unevenness of the photoreceptor as described above.
[0014] Therefore, the present inventors recognized that in order to suppress reverse fogging when a low charging bias is applied, it is necessary to control the volume resistivity of the portion of the domain exposed on the outer surface of the conductive member other than the conductive particles in the thickness direction of the conductive layer. Based on this recognition, as a result of further investigations, it was found that by using an electrophotographic conductive member (hereinafter also simply referred to as a conductive member) that satisfies the following requirements (A) and (B) as a charging member, reverse fogging can be suppressed even when a low charging bias is applied.
[0015] ·Requirements (A) An electrode is provided directly on the outer surface of the conductive member. In an environment with a temperature of 23°C and a relative humidity of 50%, an AC voltage with an amplitude of 1 V and a frequency of 1.0 Hz is applied between the outer surface of the support and the electrode. The impedance is 1.0 x 10 3 ~1.0×10 8 Being Omega. ·Requirements (B) The domain exposed on the outer surface of the electrophotographic conductive member is referred to as domain A, and in a cross section of the conductive layer of domain A in the thickness direction of the conductive layer, the minimum thickness of the conductive layer of domain A in the thickness direction is When the maximum length is Ld, a region having a thickness of 0.1×Ld on the side farthest from the support in the cross section of the domain A is defined as a first region, and a region having a thickness of 0.1×Ld on the side closest to the support in the cross section of the domain A is defined as a second region, the volume resistivity R1 of the portion of the first region that is not the conductive particles and the volume resistivity R2 of the portion of the second region that is not the conductive particles satisfy R1>R2.
[0016] Each requirement is explained in detail below.
[0017] <Requirements (A)> Requirement (A) represents the degree of conductivity of the conductive layer. A conductive member showing such an impedance value can suppress an excessive increase in the amount of discharge current when used as a charging member. As a result, it is possible to prevent the occurrence of uneven potential of charging caused by abnormal discharge. In addition, it is possible to suppress the occurrence of insufficient charging due to a shortage of the total amount of discharge charge. The impedance related to requirement (A) is preferably 1.3×10 3 ~9.2×10 7 Ω, and more preferably 5.0×10 3 ~5.0×10 7 Ω, and more preferably 1.0×10 4 ~1.0×10 7 It is Omega.
[0018] The impedance required for requirement (A) can be measured by the following method: First, in order to eliminate the effect of contact resistance between the conductive member and the measurement electrode, a low-resistance thin film is deposited on the surface of the conductive member, and the thin film is used as an electrode while the conductive support is used as a ground electrode to measure the impedance via two terminals. Examples of the method for forming the thin film include metal deposition, sputtering, application of a metal paste, application of a metal tape, etc. Among these, from the viewpoint of reducing the contact resistance with the conductive member, a method for forming a thin metal film of, for example, platinum or palladium by deposition as an electrode is preferred.
[0019] When forming a metal thin film (electrode) directly on the surface of a conductive member, it is preferable to provide a mechanism for holding a charged member to the vacuum deposition apparatus, in consideration of the ease of forming the metal thin film and the uniformity of the thin film. For a conductive member having a cylindrical cross section, it is preferable to use a vacuum deposition apparatus further provided with a rotation mechanism.
[0020] For example, for a cylindrical conductive member having a curved cross section such as a circular cross section, it may be difficult to connect the metal thin film as the measurement electrode to the impedance measuring device, so it is preferable to use the following method. Specifically, after forming a metal thin film electrode with a width of about 10 mm to 20 mm in the longitudinal direction of the conductive member, a metal sheet is wrapped around it tightly, and the metal sheet is connected to the measurement electrode protruding from the measuring device for measurement. This allows the measuring device to suitably obtain an electric signal from the conductive layer of the conductive member, and impedance measurement can be performed. The metal sheet may be any metal sheet that has an electric resistance value equivalent to that of the metal part of the connecting cable of the measuring device when measuring impedance, and for example, aluminum foil, metal tape, etc. can be used.
[0021] The impedance measuring device is an impedance analyzer, a network analyzer, a spectrum analyzer, etc., and is 1.0 x 10 7 Any device capable of measuring impedance in a frequency range up to 100 Hz may be used. Among these, it is preferable to measure impedance using an impedance analyzer, since it is in the range of electrical resistance of the conductive member. Fig. 4 shows a schematic diagram of a state in which a measurement electrode is formed on a conductive member. In Fig. 4, 41 is a conductive support, 42 is a conductive layer, 43 is a platinum vapor deposition layer which is a measurement electrode, and 44 is an aluminum sheet. Fig. 4(a) shows a perspective view, and Fig. 4(b) shows a cross-sectional view. It is important to sandwich the conductive layer 42 between the conductive support 41 and the conductor layer 43 of the measurement electrode, as shown in Fig. 4(b).
[0022] The conditions for measuring impedance are as follows. An impedance measuring device (for example, Solartron 1260, a 96W dielectric impedance measuring system manufactured by Solartron) is used to measure impedance in the frequency range of 1.0 Hz. The measurement is performed in an environment with a temperature of 23°C and a relative humidity of 50%. The amplitude of the AC voltage is 1 Vpp. The conductive member is divided into 5 equal regions in the longitudinal direction, and the above measurement is performed at one arbitrary point in each region, for a total of 5 points. The arithmetic mean value is regarded as the impedance of the conductive member. A more specific measurement procedure will be described later.
[0023] <Requirements (B)> Requirement (B) is a requirement expressing the relationship of the volume resistivity in the thickness direction of the conductive layer of the domain exposed on the outer surface of the conductive member. FIG. 5 is a schematic cross-sectional view of the vicinity of the outer surface of a conductive layer (surface layer) of a roller-shaped electrophotographic conductive member (hereinafter, also referred to as an electrophotographic roller) 500 according to one embodiment of the present disclosure. The conductive layer 501 of the electrophotographic roller 500 includes a matrix 503 and a plurality of domains 505 dispersed in the matrix 503. The domains 505 include a cross-linked product 505-1 of a second rubber and conductive particles 505-3. Although the support is not shown in FIG. 5, the support is present vertically below the conductive layer 501. At least a portion of domain 505-s among the multiple domains 505 is exposed to outer surface 500-1 of electrophotographic roller 500. That is, outer surface 500-1 of electrophotographic roller 500 is composed of matrix 503 and exposed portion of domain 505-s. Note that domain 505-s also contains a cross-linked product of the second rubber and conductive particles, but is omitted for convenience of explanation of the configuration of domain 505-s. When the maximum length of the domain 505-1 in the cross section of the conductive layer 501 of the domain 505-s in the thickness direction is Ld, the region with a thickness of 0.1×Ld on the side farthest from the support is defined as the first region 505-s1. Also, the region with a thickness of 0.1×Ld on the side closest to the support is defined as the second region 505-s2. When the volume resistivity of the portion 601 that is not the conductive particle in the first region 505-s1 is R1 and the volume resistivity of the portion 602 that is not the conductive particle in the second region is R2, as shown in FIG. 6, the domain 505-s satisfies R1>R2.
[0024] It is considered that the conductive layer exhibits electronic conductivity by the exchange of electrons between the multiple domain particles 505 from the support side to the outer surface side of the conductive layer, and finally discharge occurs from the domains 505-s exposed on the outer surface of the conductive member toward the electrophotographic photosensitive member. In this configuration, with regard to the exchange of charges between the multiple domain particles 505, the lower the volume resistivity of the domains, the more efficiently electrons can be exchanged. On the other hand, with regard to discharge from the domain 505-s exposed on the surface, the larger the volume resistivity of the domain, the easier it is to suppress uneven discharge and the easier it is to suppress the occurrence of fogging on the electrophotographic image. That is, the domain 505-s exposed on the outer surface preferably has a low volume resistivity from the viewpoint of more smoothly receiving charges from the domain 505 buried in the elastic layer, while a high volume resistivity is preferable for suppressing uneven discharge. A domain that satisfies such a contradictory relationship of volume resistivity is the domain 505-s according to the present disclosure. In the domain 505-s, the volume resistivity of the portion other than the conductive particles in the domain, i.e., the portion of the crosslinked product of the second rubber, is high in the first region and low in the second region. By increasing the volume resistivity R1 of the portion other than the conductive particles in the first region, unevenness in discharge from the domain 505-s can be suppressed. In addition, by increasing the volume resistivity R2 of the portion other than the conductive particles in the second region, it is possible to efficiently receive charges from other domains 505 buried in the conductive layer.
[0025] In requirement (B), the volume resistivity of the part of the domain other than the conductive particles is measured. The meaning is as follows. The part of the domain other than the conductive particles is the resin part in which the conductive particles are dispersed. The imparting of conductivity using an electronic conductive agent such as conductive particles is affected by the volume resistivity of the resin part in which the electronic conductive agent is dispersed. Therefore, the degree of imparting of conductivity can be evaluated by measuring the volume resistivity of the resin part in which the conductive particles are dispersed.
[0026] In addition, in requirement (B), the significance of measuring the volume resistivity of the first region and the second region is as follows. As described above, the region involved in the discharge is the first region. Also, it is considered that the region mainly involved in the transfer of electrons between the domain particle phases is mainly dominated by the second region. Therefore, by measuring the first region and the second region respectively and controlling the relationship between R1 and R2, it is possible to simultaneously suppress the uneven discharge and transfer of charges between the domain particles.
[0027] The volume resistivity R1 and the volume resistivity R2 are measured as follows. A slice (slice) of a predetermined thickness (e.g., 1 μm) containing a matrix-domain structure is cut out from the conductive layer. Examples of the method for cutting the slice include a sharp razor, a microtome, and a focused ion beam method (FIB). In the present disclosure, a microtome is used. Next, the volume resistivity R1 and the volume resistivity R2 can be measured by contacting a microprobe of a scanning probe microscope (SPM) or an atomic force microscope (AFM) with the part of the domain exposed on the outer surface of the slice other than the conductive particles. When a filler other than the conductive particles is added to the domain, the part other than the conductive particles and the filler is measured. A detailed description of the domain will be given later. The volume resistivity is measured as follows. First, one side of a flake cut from a conductive layer is grounded. Next, a microprobe (the tip of a cantilever) of a scanning probe microscope (SPM) or atomic force microscope (AFM) is brought into contact with a domain portion on the side opposite the grounded side of the flake, a DC voltage of 0.5 V is applied, and a current image is obtained. The volume resistivity is calculated from the current image and the film thickness of the flake. The volume resistivity R1 and volume resistivity R2 of a cylindrical conductive member are determined as follows. The conductive layer is divided into 5 equal parts in the longitudinal direction and then into 4 equal parts in the circumferential direction, and one thin sample is cut out from each region. For each sample, the volume resistivity r1 and volume resistivity r2 are measured in 3 domains exposed on the surface using the above-mentioned method for a total of 60 locations, and the arithmetic average values are calculated to determine the volume resistivity R1 and volume resistivity R2.
[0028] The volume resistivity R1 and the volume resistivity R2 are not particularly limited as long as R1>R2 is satisfied, but more preferably R1 / R2≧3.0 is satisfied. If R1 / R2 is 3.0 or more, discharge unevenness from the outer surface side can be suppressed, and charge supply by domain particle correlation can be achieved at the same time. The upper limit is not particularly limited, but for example, it is preferable to satisfy 30.0≧R1 / R2≧3.0, and it is more preferable to satisfy 22.0≧R1 / R2≧3.0. By having R1 / R2 be 30.0 or less, it is possible to achieve both charge reception from other domains and discharge stability at a higher level. The method for adjusting the volume resistivity R1 and the volume resistivity R2 will be described later.
[0029] The conductive member will be described with reference to Fig. 1, taking a conductive roller as an example. Fig. 1 is a cross-sectional view showing the configuration of a cross section perpendicular to the longitudinal direction, which is the axial direction, of the conductive roller. The conductive roller has a cylindrical support 11 having a conductive outer surface, and a conductive layer 12 provided on the outer circumferential surface of the support 11, i.e., on the outer surface of the support. However, in the conductive member, the shape of the support is not particularly limited.
[0030] <Support> The material constituting the support 11 may be any material known in the field of electrophotographic conductive members, or any material having a conductive property. The material may be appropriately selected from materials that can be used as conductive members, and examples thereof include metals and alloys such as aluminum, stainless steel, conductive synthetic resins, iron, and copper alloys. Furthermore, these may be subjected to an oxidation treatment or a plating treatment with chromium, nickel, or the like. As the type of plating, either electric plating or electroless plating can be used. From the viewpoint of dimensional stability, electroless plating is preferred. As the type of electroless plating used here, nickel plating, copper plating, gold plating, and various other alloy platings can be mentioned. Among them, electroless nickel plating is preferred. The plating thickness is preferably 0.05 μm or more, and considering the balance between working efficiency and rust prevention ability, the plating thickness is preferably 0.10 μm or more and 30.00 μm or less.
[0031] The shape of the cylindrical support 11 may be a solid cylindrical shape or a hollow cylindrical shape (cylindrical shape). The outer diameter of the support is preferably 3 mm or more and 10 mm or less. The length of the support in the longitudinal direction is not particularly limited, but is preferably, for example, 200 mm or more and 300 mm or less. Furthermore, if necessary, the support may be partially processed in order to be mounted on an electrophotographic image forming apparatus.
[0032] If a medium resistance layer or an insulating layer is present between the support and the conductive layer, it may be difficult to quickly supply the charge after the charge is consumed by discharge. Therefore, it is preferable to directly provide the conductive layer in a manner in which it is in contact with the support. In addition, it is also a preferable embodiment to provide the conductive layer on the outer surface of the support only through an intermediate layer made of a conductive resin layer such as a primer layer. It is more preferable that the primer layer is a thin film. As the primer, a known one can be selected and used depending on the rubber material for forming the conductive layer and the material of the support. As the material for the primer, for example, a thermosetting resin or a thermoplastic resin can be mentioned, and specifically, known materials such as a phenol resin, a urethane resin, an acrylic resin, a polyester resin, a polyether resin, and an epoxy resin can be used. Among them, a phenol resin is preferable, and for example, Metalock U-20 (manufactured by Toyo Kagaku Kenkyusho Co., Ltd.) can be used.
[0033] <Conductive layer> The conductive layer has a matrix containing a crosslinked product of the first rubber and a plurality of domains dispersed in the matrix. The outer surface of the conductive layer is composed of the matrix and exposed portions of the domains exposed on the outer surface of the conductive layer. The outer surface of the conductive layer corresponds to the outer surface of the electrophotographic conductive member. The shape of the domain is not particularly limited, but it is preferable that the domain dispersed in the matrix has few convex or concave portions on its outer peripheral surface. That is, the outer shape of the domain is preferably approximately spherical. When there are concaves and convexes on the outer peripheral surface that constitutes the outline of the domain, the charge transfer between the domains may vary in density, and the transfer of electrons from the support side of the conductive layer to the outer surface side of the conductive layer may become uneven. This is because when there are concaves and convexes on the outer peripheral surface of the domain, the charge transfer may be concentrated on the convex portions, and some places where the charge transfer is concentrated may occur at the same time, resulting in places where the charge transfer is insufficient. For the same reason, it is preferable that the proportion of domains with few convex or concave portions on the outer peripheral surface is high. The fact that the outer peripheral surface of the domain has few convexities and concaves is specifically expressed by the value of A / B being 1.00 to 1.10, where A is the perimeter of the domain and B is the envelope perimeter of the domain. In the outer peripheral surface constituting the outline of the domain having the value of A / B in this range, it can be said that the outer peripheral surface has few convexities and concaves, that is, the outer peripheral surface is smooth. The perimeter A of the domain and the envelope perimeter B of the domain are calculated by observing the domain with an observation device such as an electron microscope by the method described later. The value of A / B can be adjusted, for example, by reducing the domain diameter of the CMB or increasing the content of conductive particles in the domain.
[0034] In addition, the proportion of domains with few convexities or concaves on the outer surface is high, specifically, when the length of the conductive layer in the longitudinal direction is L and the thickness of the conductive layer is T, and when 15 μm square observation regions are placed in three locations in the thickness region from the outer surface of the conductive layer to a depth of 0.1T to 0.9T for each of the three locations (i.e., L1 / 4, L2 / 4, L3 / 4) in the cross section of the conductive layer in the thickness direction, the perimeter of the domain is A and the envelope perimeter of the domain is B, the proportion of the number of domains with an A / B value of 1.00 to 1.10 is 80% or more by number, where A is the perimeter of the domain and B is the envelope perimeter of the domain. The proportion of the number of domains with an A / B value of 1.00 to 1.10 is more preferably 82% or more by number, and even more preferably 84% or more by number. The upper limit is not particularly limited, but is preferably, for example, 80 to 100% by number, more preferably 82 to 100% by number, and even more preferably 84 to 100% by number. The ratio of the number of domains in which the A / B value is 1.00 to 1.10 can be controlled by the method described later. The arithmetic mean value of A is preferably from 0.30 to 16 μm, and more preferably from 1.2 to 9.5 μm.
[0035] <Matrix> The matrix includes a crosslinked first rubber. The volume resistivity of the matrix is 1.0×10 8 ~1.0×10 17 The volume resistivity of the matrix is preferably 1.0×10 8 By setting the resistivity at Ω·cm or more, it is possible to suppress the matrix from disturbing the exchange of charges between domains. 17 By setting the resistivity to Ω·cm or less, discharge from the conductive member to the member to be charged can be smoothly performed when a charging bias is applied between the support and the member to be charged.
[0036] The volume resistivity of the matrix, ρm, is 1.0×1010 ~1.0×10 17 Ω cm is more preferable, and even more preferable is 1.0×10 12 ~1.0×10 17 Ω·cm is preferred. The volume resistivity ρm of the matrix is measured as follows. A slice (slice) of a predetermined thickness (e.g., 1 μm) containing a matrix-domain structure is cut out from the conductive layer. Examples of the method for cutting the slice include a sharp razor, a microtome, and a focused ion beam method (FIB). In the present disclosure, a microtome is used. Next, the volume resistivity can be measured by contacting the matrix in the slice with a microprobe of a scanning probe microscope (SPM) or an atomic force microscope (AFM).
[0037] When a filler or the like is added to the matrix, the portion other than the filler is measured. Specifically, the volume resistivity is measured as follows. First, one side of a flake cut from a conductive layer is grounded. Next, a microprobe (the tip of a cantilever) of a scanning probe microscope (SPM) or atomic force microscope (AFM) is brought into contact with the matrix portion of the surface of the flake opposite the grounded surface, a DC voltage of 0.5 V is applied, and a current image is obtained. The volume resistivity is calculated from the current image and the film thickness of the flake.
[0038] The sampling positions of the slices are three in total, namely, the center in the longitudinal direction of the conductive layer and two positions at L / 4 from both ends of the conductive layer toward the center (i.e., L1 / 4, L2 / 4, L3 / 4), where L is the longitudinal length of the conductive layer. Next, the measurement positions are three in the matrix portion of each slice in a thickness region from the outer surface to a depth of 0.1T to 0.9T, where T is the thickness of the conductive layer, for a total of nine positions. The volume resistivity is measured at these measurement positions, and the arithmetic average value is taken as the volume resistivity of the matrix. The volume resistivity ρm of the matrix is small for materials with small solubility parameters such as natural rubber (NR), isoprene rubber (IR), and ethylene propylene diene terpolymer rubber (EPDM). The volume resistivity ρm of the matrix can be increased by using a non-polar rubber as the first rubber. The volume resistivity ρm of the matrix can be decreased by using a polar rubber such as chloroprene rubber (CR) or acrylonitrile butadiene rubber (NBR) with a large solubility parameter.
[0039] <First Rubber> The first rubber is the component with the highest compounding ratio in the rubber composition for forming the conductive layer, and the first rubber governs the mechanical strength of the conductive layer. Therefore, the first rubber is one that exhibits the strength required for the electrophotographic conductive member in the conductive layer after crosslinking. Preferable examples of the first rubber are as follows: natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), butyl rubber (IIR), ethylene-propylene rubber (EPM), ethylene propylene diene terpolymer rubber (EPDM), chloroprene rubber (CR), acrylonitrile butadiene rubber (NBR), hydrogenated NBR (H-NBR), and silicone rubber.
[0040] The first rubber is more preferably at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM), and further preferably at least one selected from the group consisting of styrene-butadiene rubber (SBR) and acrylonitrile butadiene rubber (NBR).
[0041] The first rubber forming the matrix can contain a reinforcing material to the extent that it does not affect the electrical conductivity. An example of the reinforcing material is reinforcing carbon black with low electrical conductivity. Specific examples of reinforcing carbon black include FEF, GPF, SRF, and MT carbon.
[0042] Furthermore, the first rubber may contain, as necessary, fillers such as calcium carbonate; processing aids such as zinc stearate; vulcanization aids; vulcanization accelerators such as tetrabenzyl thiuram disulfide, tetramethyl thiuram monosulfide, N-cyclohexyl-2-benzothiazolylsulfenamide, and 2-mercaptobenzimidazole; vulcanization acceleration aids such as zinc oxide; vulcanization retarders; antioxidants; softeners; dispersants; colorants; roughening particles, etc.
[0043] The SP value of the first rubber is not particularly limited, but is preferably 15.0 to 23.0, and more preferably 16.0 to 22.0. By being within the above range, the absolute value of the difference in solubility parameter between the first rubber and the second rubber can be easily adjusted to the range described below.
[0044] <domain> The domain includes a crosslinked product of the second rubber and conductive particles. Here, the conductive particles are conductive when the volume resistivity is 1.0×10 8 It is defined as less than Ω·cm. At least a portion of the plurality of domains are exposed on the outer surface of the electrophotographic conductive member. In addition, when the impedance and the volume resistivity ρm of the matrix related to the above-mentioned requirement (A) are satisfied, electrons are transferred between the multiple domains from the conductive support side, and finally, electrons are emitted from the domains exposed on the surface of the conductive member, thereby exhibiting electronic conductivity. Therefore, an amount of domains that can obtain the effects of the present disclosure is exposed on the outer surface. As described above, by satisfying the requirements (A) and (B), it is possible to suppress inversion fog even when a low charging bias is applied.
[0045] <Second Rubber> Specific examples of the second rubber include at least one selected from the group consisting of natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), acrylonitrile butadiene rubber (NBR), styrene butadiene rubber (SBR), butyl rubber (IIR), ethylene propylene rubber (EPM), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (H-NBR), silicone rubber, and urethane rubber (U).
[0046] The second rubber is more preferably at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM), and is even more preferably at least one selected from the group consisting of styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM). In addition, the second rubber is preferably different from the first rubber.
[0047] The SP value of the second rubber is not particularly limited, but is preferably 15.0 to 23.0, and more preferably 16.0 to 22.0. By being in the above range, the absolute value of the difference in solubility parameter between the first rubber and the second rubber can be easily adjusted to the range described below.
[0048] <Conductive particles> Examples of conductive particles include carbon materials such as conductive carbon black and graphite, conductive oxides such as titanium oxide and tin oxide, metals such as Cu and Ag, and particles of electronic conductive agents such as particles that have been made conductive by coating the surface with a conductive oxide or metal. Two or more types of these conductive particles may be used in appropriate amounts. In the domain observed in the cross section in the thickness direction of the conductive layer, the ratio S of the cross-sectional area of the conductive particles contained in the domain to the cross-sectional area of the domain is cIt is preferable that / S is 20.0 area % or more. By filling the domain with conductive particles at a high density in this manner, it is easy to reduce the unevenness of the outer peripheral surface of the domain. c The upper limit of / S is not particularly limited, but is preferably 35.0% by area or less. For example, S c / S is 20.0 to 35.0 area %, 25.0 to 35.0 area %, or 26.0 to 33.0 area %.
[0049] In order to obtain a domain in which the conductive particles are densely packed, it is preferable to use conductive carbon black as the conductive particles. That is, it is preferable that the conductive particles contain carbon black. The carbon black is preferably at least one selected from the group consisting of gas furnace black, oil furnace black, thermal black, lamp black, acetylene black, and ketjen black.
[0050] Among them, DBP absorption is 40-80 cm 3 Carbon black having a DBP absorption capacity (cm 3 / 100g) is the volume of dibutyl phthalate (DBP) that can be adsorbed by 100g of carbon black, and is measured in accordance with Japanese Industrial Standards (JIS) K6217-4:2017 (Carbon black for rubber - Basic properties - Part 4: Determination of oil absorption (including compressed samples)). Generally, carbon black has a cluster-like higher-order structure in which primary particles with an average particle size of 10 nm to 50 nm are aggregated. This cluster-like higher-order structure is called structure, and its degree is expressed as DBP absorption (cm 3 / 100g).
[0051] Generally, carbon black with a developed structure has a high reinforcing effect on rubber, is difficult to incorporate into rubber, and has a very high shear torque during kneading, making it difficult to increase the amount of carbon black loaded in the domain. On the other hand, conductive carbon black with DBP absorption within the above range has an underdeveloped structure, so carbon black aggregates less and disperses well in rubber, allowing a larger amount of carbon black to be filled into the domain, which in turn makes it easier to obtain a domain with a more spherical outer shape.
[0052] Furthermore, carbon black with a developed structure tends to aggregate with itself, and the aggregates tend to form lumps with large unevenness. On the other hand, conductive carbon black with DBP absorption within the above range is preferred for obtaining a domain with less unevenness on the outer circumferential surface, since it is difficult to form aggregates. The content of conductive particles such as conductive carbon black is preferably 20 to 150 parts by mass relative to 100 parts by mass of the second rubber contained in the domain. More preferably, it is 50 to 100 parts by mass.
[0053] The volume resistivity of the domain is 1.0×10 4 It is preferable to keep it below 1.0×10 4 If the resistivity is Ω·cm or less, the domain can be made conductive easily even at a volume fraction that stably forms a matrix-domain structure. The lower limit of the volume resistivity of the domain is not particularly limited, but is, for example, 1.0×10 1 ~1.0×10 4 Ω cm, 5.0×10 1 ~1.0×10 4 It may be Ω·cm. The volume resistivity of the domain is measured in the same manner as in the measurement of the volume resistivity of the matrix, except that the measurement is carried out at a location of the ultrathin slice that corresponds to the domain.
[0054] <Method of manufacturing conductive layer> The conductive layer of the conductive member can be formed, for example, through a method including the following steps (i) to (iv). Step (i): A step of preparing a domain-forming rubber composition (hereinafter also referred to as "CMB") containing conductive particles and a second rubber. Step (ii): preparing a matrix-forming rubber composition (hereinafter also referred to as "MRC") containing a first rubber. Step (iii): A step of kneading CMB and MRC to prepare a rubber composition for forming a conductive layer having a matrix-domain structure. Step (iv): A step of forming a layer of the rubber composition for forming a conductive layer prepared in step (iii) on a support directly or via another layer, and curing the layer of the rubber composition to form a conductive layer.
[0055] The mixing ratio of CMB and MRC in the rubber composition for forming the conductive layer (CMB:MRC) based on mass is preferably 10:90 to 40:60, more preferably 20:80 to 30:70. The rubber composition for forming the conductive layer may contain known additives such as a vulcanizing agent and a vulcanization accelerator, if necessary. The conductive layer is, for example, a crosslinked product (vulcanizate) of the rubber composition for forming the conductive layer.
[0056] The conductive particles used in the preparation of CMB preferably have a DBP absorption of 40 to 170 cm 3 / 100g, more preferably 40-90cm 3 It is effective to add a large amount of carbon black having a molecular weight of 1000 g / 100 g to the second rubber and knead it to prepare the CMB. In this case, the amount of carbon black to be mixed with the second rubber in the CMB is preferably, for example, 40 to 200 parts by mass per 100 parts by mass of the second rubber. In particular, it is 50 to 100 parts by mass.
[0057] The ratio of the cross-sectional area of the conductive particles contained in the domain to the domain cross-sectional area S c / S may be measured as follows. First, a thin piece of the conductive layer is prepared. In order to favorably observe the matrix-domain structure, the piece may be subjected to pretreatment such as dyeing or deposition treatment that favorably provides contrast between the conductive phase and the insulating phase.
[0058] The formed and pretreated thin section can be observed with a scanning electron microscope (SEM) or a transmission electron microscope (TEM). Among these, it is preferable to observe with an SEM at 1,000 to 100,000 magnifications in terms of the accuracy of quantifying the area of the domains that are the conductive phase. The above ratio can be obtained by binarizing and analyzing the obtained observation image using an image analyzer or the like. Specific means will be described later.
[0059] In order to further reduce the electric field concentration between the domains, it is preferable to make the outer shape of the domain closer to a sphere. For example, in the process of preparing a rubber composition in which MRC and CMB are mixed and phase-separated to form a CMB domain in the MRC matrix, the domain diameter of the CMB is controlled to be small. By reducing the domain diameter of the CMB, the total specific surface area of the CMB increases, and the interface with the matrix increases, so that a tension that tries to reduce the tension acts on the interface of the CMB domain. As a result, the outer shape of the CMB domain becomes closer to a sphere.
[0060] Here, the Taylor formula (formula (1)), Wu's empirical formula (formulas (2) and (3)), and Tokita's formula (formula (4)) are known to determine the domain diameter D in the matrix-domain structure formed when two incompatible polymers are melt-kneaded. (Sumitomo Chemical Technical Journal 2003-II, 42) · Taylor's formula D=[C·σ / ηm·γ]·f(ηm / ηd) (1) ·Wu's Empirical Formula γ D ηm / σ = 4(ηd / ηm) 0.84 ηd / ηm>1 (2) γ D ηm / σ = 4(ηd / ηm) -0.84 ηd / ηm<1 (3)
[0061] ·Tokita's Ceremony
number
[0062] In equations (1) to (4), D is the domain diameter of the CMB (maximum Feret diameter Df), C is a constant, σ is the interfacial tension, ηm is the viscosity of the matrix, and ηd is the viscosity of the domain. In equation (4), γ is the shear rate, η is the viscosity of the mixture, P is the probability of collision and coalescence, φ is the domain phase volume, and EDK is the domain phase breakage energy.
[0063] From the above formulas (1) to (4), it is effective to control the physical properties of CMB and MRC and the kneading conditions in step (iii) in order to reduce the domain diameter D of CMB. Specifically, it is effective to control the following four items (a) to (d). (a) Difference in interfacial tension σ between the CMB and the MRC; (b) The ratio (ηm / ηd) of the viscosity of the CMB (ηd) and the viscosity of the MRC (ηm); (c) Shear rate (γ) and energy content (EDK) during kneading of CMB and MRC in step (iii); (d) Volume fraction of CMB in the mixture of CMB and MRC in step (iii)
[0064] (a) Interfacial tension difference between CMB and MRC Generally, when two incompatible rubbers are mixed, phase separation occurs. This is because the interaction between the same polymers is stronger than the interaction between different polymers, so the same polymers aggregate together and the free energy is lost. This is to lower and stabilize the energy. The interface of the phase separation structure comes into contact with different polymers, so the free energy is higher than the interior, which is stabilized by the interaction between the same molecules. As a result, in order to reduce the free energy of the interface, interfacial tension is generated that tries to reduce the area of contact with the different polymers. When this interfacial tension is small, the different polymers tend to mix more uniformly in order to increase the entropy. The state of uniform mixing is dissolution, and the SP value, which is an indicator of solubility, tends to correlate with the interfacial tension. In other words, it is thought that the difference in interfacial tension between CMB and MRC correlates with the difference in SP value between CMB and MRC. Therefore, it is possible to control it by the combination of MRC and CMB, especially the combination of the first rubber and the second rubber.
[0065] For the first rubber in the MRC and the second rubber in the CMB, the absolute value of the difference in solubility parameter (SP value) between the first rubber and the second rubber is 0.4 to 5.7 (J / cm 3 ) 0.5 More preferably, the absolute value of the difference in the SP value is 0.4 to 5.0 (J / cm 3 ) 0.5 More preferably, the absolute value of the difference in SP value is 0.4 to 4.7 (J / cm 3 ) 0.5 It is particularly preferable that the absolute value of the difference in the SP value is 0.4 to 3.2 (J / cm 3 ) 0.5 It is particularly preferable that the absolute value of the difference in the SP value is 0.4 to 1.0 (J / cm 3 ) 0.5 It is a combination such that:
[0066] By using a combination of rubbers in which the absolute value of the difference in SP value falls within the above range, a phase separation structure can be formed more stably, and the domain diameter D of the CMB can be reduced. SP value of the first rubber (J / cm 3 ) 0.5 is preferably from 16.0 to 22.0, and more preferably from 17.0 to 21.7. SP value of the second rubber (J / cm 3 ) 0.5 is preferably from 16.0 to 22.0, more preferably from 16.0 to 20.0.
[0067] As a preferable combination of the first rubber and the second rubber, on the premise that the absolute value of the difference in SP value is within the above range, for example, the combinations described in Table 1 below can be mentioned. [Table 1]
[0068] <Method for measuring SP value> The SP values of the first rubber and the second rubber contained in each of MRC and CMB can be accurately calculated by creating a calibration curve using a material with a known SP value. As this known SP value, the catalog value of the material manufacturer can also be used. For example, NBR and SBR are independent of the molecular weight, and the SP value is almost determined by the content ratio of acrylonitrile or styrene. Therefore, the rubbers constituting the matrix and the domain are analyzed for the content ratio of acrylonitrile or styrene using analytical methods such as pyrolysis gas chromatography (Py-GC) and solid NMR. Then, the SP value can be calculated based on the content ratio from the calibration curve obtained from a material with a known SP value. Also, for isoprene rubber, the SP value is determined by the isomeric structure such as 1,2-polyisoprene, 1,3-polyisoprene, 3,4-polyisoprene, cis-1,4-polyisoprene, and trans-1,4-polyisoprene. Therefore, similar to SBR and NBR, the isomer content ratio is analyzed by Py-GC and solid NMR, etc., and the SP value can be calculated from a material with a known SP value. The SP value of the material with a known SP value is obtained by the Hansen sphere method.
[0069] (b) Viscosity ratio of CMB and MRC The closer the viscosity ratio (ηd / ηm) between CMB and MRC is to 1, the smaller the maximum Feret diameter of the domains can be. The viscosity ratio between CMB and MRC can be adjusted by selecting the Mooney viscosity of CMB and MRC, and by mixing the type and amount of filler. It can also be adjusted by adding a plasticizer such as paraffin oil to an extent that does not interfere with the formation of a phase separation structure. The viscosity ratio can also be adjusted by adjusting the temperature during kneading. The viscosity of CMB and MRC is measured using the Mooney viscosity ML (1+4) It can be obtained by measuring the rubber temperature during kneading.
[0070] (c) Shear rate and energy during mixing of MRC and CMB The faster the shear rate during kneading of MRC and CMB, and the greater the amount of energy during shearing, the smaller the maximum Feret diameter Df of the domains can be.
[0071] The shear rate can be increased by increasing the inner diameter of the mixing member, such as the blade or screw of the mixer, decreasing the gap between the end face of the mixing member and the inner wall of the mixer, or by increasing the rotation speed. In addition, the energy during shear can be increased by increasing the rotation speed of the mixing member or by increasing the viscosity of the first rubber in the CMB and the second rubber in the MRC.
[0072] (d) Domain volume fraction (volume fraction of CMB in the mixture of CMB and MRC) The volume fraction of CMB in the mixture of CMB and MRC correlates with the probability of collision and merging of CMB with MRC. Specifically, reducing the volume fraction of CMB in the mixture of CMB and MRC decreases the probability of collision and merging of CMB and MRC. In other words, the size of the domain can be reduced by reducing the volume fraction of the domain in the conductive layer within the range where the required conductivity is obtained.
[0073] <How to confirm matrix-domain (MD) structure> The matrix-domain structure can be confirmed, for example, by the following method. That is, a thin piece of the conductive layer is cut out from the conductive layer to prepare an observation sample. Examples of the means for cutting out the thin piece include a razor, a microtome, and an FIB. If necessary, the observation sample is subjected to a treatment (e.g., a staining treatment or a deposition treatment) that can facilitate the distinction between the matrix and the domain. The observation sample is then observed using a laser microscope, SEM, or TEM. A more specific procedure will be described later.
[0074] <Method of measuring domain perimeter, envelope perimeter, number of domains and average number of domains> The domain perimeter, envelope perimeter, and the number and average number of domains can be measured, for example, as follows. First, a section is prepared using the same method as in the measurement of the volume resistivity of the matrix described above. Then, the section is subjected to a freeze fracture method, a cross polisher method, a focused ion beam (FIB) method, etc. A thin piece having a fracture surface can be formed by the above means. Considering the smoothness of the fracture surface and pretreatment for observation, the FIB method is preferred. In order to favorably observe the matrix-domain structure, a pretreatment such as a dyeing treatment or a deposition treatment may be performed to favorably obtain a contrast between the conductive phase and the insulating phase.
[0075] The formed and pretreated thin sections can be observed by SEM or TEM. Among these, it is preferable to observe with SEM at 1,000 to 100,000 magnifications in terms of the accuracy of quantifying the domain perimeter and envelope perimeter.
[0076] The perimeter, envelope perimeter, and number of domains of a domain can be measured by quantifying the captured image as described above. The fracture surface image obtained by observation with an SEM is converted to 8-bit grayscale using image processing software such as Image-Pro Plus (manufactured by Planetron Corporation) to obtain a monochrome image with 256 gradations. Next, the image is inverted to black and white so that the domains in the fracture surface become white, and binarized. Next, the perimeter, envelope perimeter, and number of domains can be calculated from each of the domain groups in the image. More specific means will be described later.
[0077] For the above measurement, the sample is cut out from a total of three locations (i.e., L1 / 4, L2 / 4, and L3 / 4) including the center of the longitudinal direction of the conductive layer of the conductive member and two locations of L / 4 from both ends of the conductive layer toward the center, where the length of the longitudinal direction of the conductive layer is L. The direction in which the slices are cut out is a direction that forms a cross section perpendicular to the longitudinal direction of the conductive layer. Regarding the observation position of each slice cross section, when the thickness of the conductive layer is T, measurements are performed in a total of nine observation regions, where 15 μm square observation regions are placed in three locations in the thickness region from the outer surface of each slice to a depth of 0.1T to 0.9T. The arithmetic average value of the measured values obtained in the nine observation regions is taken as the measurement result.
[0078] <How to achieve requirement (B)> The method for achieving the requirement (B) is not particularly limited as long as the volume resistivity R1 and the volume resistivity R2 satisfy the relationship R1>R2. Specific methods include, for example, an impregnation process and a method of adding a material that migrates to the surface to the material for forming the conductive layer. More specifically, an impregnation process that can increase the resistance only in the vicinity of the outer surface of the conductive layer is preferable. The impregnation treatment is a treatment in which a monomer is impregnated from the surface of a conductive layer precursor such as a conductive resin layer, and then the monomer is cured. A resin that is a cured product of the monomer is also called a curable resin.
[0079] By performing the impregnation treatment, the curable resin is present in the gaps between the matrix forming the conductive layer surface and the rubber constituting the domain. As a result, the distance between the conductive particles present in the domain is widened by the curable resin, and the resistance becomes high. In addition, since the curable resin generally has a high volume resistivity, the resin part constituting the matrix also becomes highly resistive. Furthermore, the formation of a network derived from the curable resin in the rubber also reduces the ionic conductivity derived from the impurities contained in the rubber. Therefore, it is considered that the volume resistivity of the rubber increases. In other words, the volume resistivity R1 of the part other than the conductive particles in the first region tends to be larger than the volume resistivity R2 of the part other than the conductive particles in the second region. From the above-mentioned action and effect, the requirement (B) can be achieved by carrying out an impregnation treatment on a conductive layer having a matrix-domain structure in which domains containing the cross-linked product of the second rubber and conductive particles are dispersed in a matrix containing the cross-linked product of the first rubber, and in which the domains are exposed on the surface.
[0080] In addition to achieving requirement (B), the impregnation treatment also reduces the adhesion of dirt to the surface of the conductive member. The reason for this is unclear, but it is thought that the curable resin penetrates between the rubber that constitutes the matrix and the domain. It is believed that the presence of the conductive layer in the gaps changes the surface characteristics of the conductive layer, reducing the adhesive force with contaminant components such as developer and external additives present on the photoreceptor surface.
[0081] The method of impregnation is not particularly limited, but includes spraying with a paint containing a solvent added to the raw material, immersion (dipping coating method), and roll coating. The dip coating method is preferred because it is simple and has excellent production stability. In addition, in order to polymerize the monomer after coating, it is preferable to perform additional treatment such as heating or light irradiation as necessary. The region of the conductive layer that is impregnated can be controlled by the type of monomer to be impregnated, the type of solvent in which the monomer is dissolved, the monomer concentration, the immersion time, and the like. As the impregnation treatment region, it is preferable that it is a region less than the above-described second region from the outer surface of the conductive member in order to suppress uneven discharge from the outer surface side of the conductive member and to achieve both charge supply between domain particles. That is, it is preferable that the above-described second region is not impregnated.
[0082] When performing an impregnation treatment using a monomer that does not react or hardly reacts with rubber, it is considered that an interpenetrating polymer network structure is formed. Hereinafter, the interpenetrating polymer network structure may be referred to as an "IPN structure". Since the crosslinked rubber and the curable resin constituting the IPN structure basically do not have a chemical bond, it is more preferable because it is easy to maintain rubber elasticity. That is, it is more preferable that the curable resin constitutes an interpenetrating polymer network structure together with the first rubber and the second rubber.
[0083] <Method for confirming IPN structure> In order to confirm that the IPN structure is formed, methods for confirmation include a method using a scanning electron microscope (SEM) or a transmission electron microscope (TEM), a method using solvent extraction, and a method using a shift in the glass transition point before and after forming the IPN structure. In the present disclosure, confirmation is performed using a transmission electron microscope (TEM). Specific means will be described later. That is, a thin piece of the conductive layer is cut out from the conductive layer to prepare an observation sample. Examples of the cross-sectioning method include a sharp razor, a microtome, and a focused ion beam method (FIB). For the observation sample, a treatment (for example, a staining treatment, a vapor deposition treatment) that can facilitate the distinction between rubber and the curable resin is performed as necessary. Then, observation is performed by TEM. Among these, from the viewpoint of accuracy, it is preferable to perform observation with TEM at a magnification of 1,000 to 100,000 times.
[0084] 〈Monomer〉 The monomer used in the impregnation treatment is preferably a polyfunctional monomer having a plurality of functional groups having curability in order to form a crosslinked structure. Also, monofunctional monomers may be used in combination as necessary. Specific examples of monomers used in the impregnation treatment include acrylic acid esters, methacrylic acid esters, vinyl ethers, epoxides, isocyanates, etc. Among them, (meth)acrylic acid esters are preferred because of their high reactivity and high insulating properties. The (meth)acrylic acid esters referred to here refer to acrylic acid esters and methacrylic acid esters.
[0085] The (meth)acrylic acid ester is selected from known and commonly used esters, and examples thereof include the following. Diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, PO-modified neopentyl glycol di(meth)acrylate, Bifunctional (meth)acrylates such as polyethylene glycol di(meth)acrylate, trifunctional (meth)acrylates such as trimethylolpropane ethoxy tri(meth)acrylate and glycerin propoxy tri(meth)acrylate, and tetrafunctional (meth)acrylates such as pentaerythritol tetra(meth)acrylate, pentaerythritol tetraethoxy (meth)acrylate and trimethylolpropane tetra(meth)acrylate. Among these, at least one selected from the group consisting of PO-modified neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate is preferred.
[0086] The vinyl ether monomer is selected from known and commonly used ones, and examples thereof include the following: bifunctional vinyl ethers such as 1,4-butanediol divinyl ether and cyclohexanedimethanol divinyl ether. Among them, cyclohexanedimethanol divinyl ether is preferred. The epoxide monomer is selected from commonly used known ones, and examples thereof include the following: bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, resorcinol diglycidyl ether, etc. Among them, hydrogenated bisphenol A diglycidyl ether is preferred.
[0087] The isocyanate monomer is selected from known and commonly used ones, for example, the following: toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymeric diphenylmethane polyisocyanate, polymeric polyphenylene polyisocyanate, hydrogenated MDI, xylylene diisocyanate (XDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), etc. Among these, at least one selected from the group consisting of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymeric diphenylmethane polyisocyanate, and polymeric polyphenylene polyisocyanate is preferred, and polymeric polyphenylene polyisocyanate is more preferred.
[0088] The monomer can be identified by using infrared spectroscopy (IR) or pyrolysis gas chromatography-mass spectrometry (Pyr-GCMS).
[0089] A known method can be used for polymerizing the monomer. Specific examples include thermal polymerization by heating and photopolymerization such as ultraviolet irradiation. A known radical polymerization initiator or ionic polymerization initiator can be used for each polymerization method. Examples of the thermal polymerization initiator for thermal polymerization include peroxides such as 3-hydroxy-1,1-dimethylbutylperoxyneodecanoate, α-cumylperoxyneodecanoate, t-butylperoxyneoheptanoate, t-butylperoxypivalate, t-amylperoxynormaloctoate, t-butylperoxy2-ethylhexylcarbonate, dicumylperoxide, di-t-butylperoxide, di-t-amylperoxide, 1,1-di(t-butylperoxy)cyclohexane, and n-butyl-4,4-di(t-butylperoxy)valerate; Examples of azo compounds include 2,2-azobisbutyronitrile, 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(2-methylbutyronitrile), 1,1-azobis(cyclohexane-1-carbonitrile), 2,2-azobis[2-(2-imidazolin-2-yl)propane], 2,2-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2-azobis(N-butyl-2-methoxypropionamide), and dimethyl-2,2-azobis(isobutyrate).
[0090] Examples of photoradical generators for photopolymerization by irradiation with ultraviolet light include 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methylpropan-1-one, and the like. 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0091] Examples of photocationic polymerization initiators for photopolymerization by irradiation with ultraviolet light include 4-methylphenyl-4-(2-methylpropyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(2-methylpropyl)phenyliodonium hexafluoroantimonate, 4-methylphenyl-4-(2-methylpropyl)phenyliodonium tetrafluoroborate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluoroantimonate, triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrafluoroborate, bis[4-(diphenylsulfonio)phenyl]sulfide bishexafluorophosphate, tetraphenylphosphonium hexafluorophosphate, tetraphenylphosphonium hexafluoroantimonate, and tetraphenylphosphonium tetrafluoroborate. These polymerization initiators may be used alone or in combination of two or more kinds.
[0092] In addition, the amount of the polymerization initiator is preferably 0.5 to 10 parts by mass when the total amount of compounds for forming a specific resin such as the above-mentioned monomers (for example, compounds having a (meth)acryloyl group) is 100 parts by mass, from the viewpoint of efficiently progressing the reaction.
[0093] Known devices for heating and ultraviolet irradiation can be used as appropriate. As a light source for irradiating ultraviolet rays, for example, an LED lamp, a high-pressure mercury lamp, a metal halide lamp, a xenon lamp, and a low-pressure mercury lamp can be used. The integrated light amount required for polymerization can be appropriately adjusted depending on the type and amount of the compound and polymerization initiator used.
[0094] It is preferable that the domain exposed on the outer surface of the conductive member further contains at least one resin selected from the group consisting of (meth)acrylic resin, epoxy resin, vinyl ether resin, and urea resin. Among them, (meth)acrylic resin is more preferable. For example, the above-mentioned monomer can be used during the above-mentioned impregnation treatment to allow the domain to contain the resin. For example, the (meth)acrylic resin is a polymer of (meth)acrylic acid ester, the epoxy resin is a polymer of epoxide, the vinyl ether resin is a polymer of vinyl ether, and the urea resin is a polymer of isocyanate and amine. As described above, the resin preferably forms an interpenetrating polymer network together with the first rubber and the second rubber.
[0095] It is preferable that the first region further contains at least one resin selected from the group consisting of (meth)acrylic resins, epoxy resins, vinyl ether resins, and urea resins. For example, the above-mentioned monomer may be used in the above-mentioned impregnation treatment to allow the first region to contain the resin. As described above, the resin preferably forms an interpenetrating polymer network together with the first rubber and the second rubber. Furthermore, it is preferable that the second region does not contain the resin. This makes it easier to achieve requirement (B). Methods for preventing the second region from containing the resin include, for example, changing the composition of the impregnation paint or changing the impregnation time. The absence of the resin in the second region can be confirmed by the method described below.
[0096] <Process cartridge> At least one aspect of the present disclosure provides a process cartridge having the electrophotographic conductive member of the present disclosure. Fig. 2 is a schematic cross-sectional view of an electrophotographic process cartridge 100 having the conductive member according to one embodiment of the present disclosure as a charging roller. This process cartridge is configured to be detachably attached to the main body of an electrophotographic image forming apparatus, with a developing device and a charging device integrated together.
[0097] The developing device is an integrated unit of at least a developing roller 103, a toner container 106, and a toner 109, and may also include a toner supply roller 104, a developing blade 108, and an agitating blade 110 as necessary.
[0098] The charging device is an integrated device of at least the photosensitive drum 101 and the charging roller 102, and may include a cleaning blade 105 and a waste toner container 107. The charging roller 102, the developing roller 103, the toner supply roller 104, and the developing blade 108 are each configured to have a voltage applied thereto.
[0099] In addition, the conductive member according to the present disclosure can be used as a charging roller, a developing roller, a developing blade, and a toner supply roller. The conductive member is preferably a charging member, and more preferably a charging roller.
[0100] <Electrophotographic image forming apparatus> At least one aspect of the present disclosure provides an electrophotographic image forming apparatus including the electrophotographic member of the present disclosure. Fig. 3 is a schematic diagram of an electrophotographic image forming apparatus 200 using the conductive member according to one embodiment of the present disclosure as a charging roller. This apparatus is a color electrophotographic apparatus in which the process cartridge 100 is detachably mounted. Each process cartridge uses toner of each color: black BK, magenta M, yellow Y, and cyan C.
[0101] The photosensitive drum 201 rotates in the direction of the arrow, is uniformly charged by a charging roller 202 to which a voltage is applied from a charging bias power supply, and an electrostatic latent image is formed on the surface by exposure light 211. Meanwhile, toner 209 stored in a toner container 206 is supplied to a toner supply roller 204 by an agitating blade 210 and transported onto a developing roller 203. Then, the toner 209 is uniformly coated on the surface of the developing roller 203 by a developing blade 208 arranged in contact with the developing roller 203, and the toner 209 is charged by frictional charging. The electrostatic latent image is developed by the toner 209 transported by the developing roller 203 arranged in contact with the photosensitive drum 201, and is visualized as a toner image.
[0102] The visualized toner image on the photosensitive drum is transferred by a primary transfer roller 212 to which a voltage is applied by a primary transfer bias power supply, onto an intermediate transfer belt 215 supported and driven by a tension roller 213 and an intermediate transfer belt drive roller 214. The toner images of each color are superimposed in order to form a color image on the intermediate transfer belt.
[0103] A transfer material 219 is fed into the apparatus by a paper feed roller, and is transported between an intermediate transfer belt 215 and a secondary transfer roller 216. A voltage is applied to the secondary transfer roller 216 from a secondary transfer bias power supply, and the secondary transfer roller 216 transfers the color image on the intermediate transfer belt 215 onto the transfer material 219. The transfer material 219 onto which the color image has been transferred is fixed by a fixing device 218, and is then discarded outside the apparatus, completing the printing operation.
[0104] Meanwhile, the toner remaining on the photosensitive drum without being transferred is scraped off by a cleaning blade 205 and stored in a waste toner storage container 207, and the above-mentioned process is repeated for the cleaned photosensitive drum 201. In addition, the toner remaining on the primary transfer belt without being transferred is also scraped off by a cleaning device 217.
[0105] Although a color electrophotographic device is shown as an example, in a monochrome electrophotographic device (not shown), the process cartridge uses only black toner. A monochrome image is formed directly on the transfer material by the process cartridge and the primary transfer roller (no secondary transfer roller) without the intermediate transfer belt. The image is then fixed by the fixing device and the paper is discharged outside the device, completing the printing operation. EXAMPLES
[0106] The present disclosure will be described below based on examples, but the technical scope of the present disclosure is not limited to these.
[0107] The charging members in the present disclosure were prepared using the materials shown below. <Elastic layer forming material> <nbr> NBR (1) (Product name: JSR NBR N230SV, acrylonitrile content: 35%, Mooney viscosity ML) (1+4) 100℃: 32, SP value: 20.0 (J / cm 3 ) 0.5 , manufactured by JSR, abbreviation: N230SV) NBR (2) (Product name: Nipol DN401LL, acrylonitrile content: 18.0%, Mooney viscosity ML (1+4) 100℃: 32, SP value: 17.4 (J / cm 3 ) 0.5 , manufactured by Zeon Corporation, abbreviation: DN401LL) NBR (3) (Product name: JSR NBR N215SL, acrylonitrile content: 48%, Mooney viscosity ML) (1+4) 100℃: 45, SP value: 21.7 (J / cm 3 ) 0.5 , manufactured by JSR, abbreviation: N215SL)
[0108] <sbr> SBR (1) (product name: Tufden 2000R, styrene content: 25%, Mooney viscosity ML (1+4) 100℃: 45, SP value: 17.0 (J / cm 3 ) 0.5 , manufactured by Asahi Kasei Corporation, abbreviation: T2000R) SBR (2) (product name: Tufden 2003, styrene content: 25%, Mooney viscosity ML) (1+4) 100℃: 33, SP value: 17.0 (J / cm 3 ) 0.5 , manufactured by Asahi Kasei Corporation, abbreviation: T2003)
[0109] <epdm> EPDM (product name: Esprene505A, Mooney viscosity ML (1+4) 100℃: 47, SP value: 16.0 (J / cm 3 ) 0.5 (Manufactured by Sumitomo Chemical Co., Ltd., abbreviation: E505A)
[0110] <Butadiene rubber BR> Butadiene rubber (product name: UBEPOL BR130B, Mooney viscosity ML) (1+4) 100℃: 29, SP value: 16.8 (J / cm 3 ) 0.5 , manufactured by Ube Industries, abbreviation: BR1 30B)
[0111] <Isoprene rubber IR> Isoprene rubber (product name: Nipol 2200L, Mooney viscosity ML) (1+4) 100℃: 70, SP value: 16.5 (J / cm 3 ) 0.5 , manufactured by Zeon Corporation, abbreviation: 2200L)
[0112] <Hydrin rubber EO-EP-AGE ternary compound (GECO)> Hydrin rubber (product name: Epichromer CG102, Mooney viscosity ML) (1+4) 100℃: 55, SP value: 18.5 (J / cm 3 ) 0.5 , manufactured by Osaka Soda Co., Ltd., abbreviation: CG102)
[0113] <Conductive particles> Carbon black (1) (Product name: Toka Black #7270SB, DBP absorption capacity: 62 cm 3 / 100g, Tokai Carbon Co., Ltd., abbreviation: #7270) Carbon black (2) (Product name: Toka Black #7360SB, DBP absorption capacity: 87 cm 3 / 100g, manufactured by Tokai Carbon Co., Ltd., abbreviation: #7360) Carbon black (3) (Product name: Raven 1170, DBP absorption capacity: 55 cm 3 / 100g, manufactured by Columbia Chemical Co., abbreviation: R1170)
[0114] <Vulcanizing agent> Vulcanizing agent (product name: SULFAX PMC, sulfur content 97.5%, manufactured by Tsurumi Chemical Industry Co., Ltd., abbreviation: sulfur)
[0115] <Vulcanization accelerator> Vulcanization accelerator (1) (product name: Suncerer TBZTD, tetrabenzyl thiuram disulfide, manufactured by Sanshin Chemical Industry Co., Ltd., abbreviation: TBzTD) Vulcanization accelerator (2) (product name: Noccela EP-60, vulcanization accelerator mixture, manufactured by Ouchi Shinko Chemical Industry Co., Ltd., abbreviation: EP-60) Vulcanization accelerator (3) (trade name: Noccela TBT, tetrabutyl thiuram disulfide, manufactured by Ouchi Shinko Chemical Industry Co., Ltd., abbreviation: TBT) Vulcanization accelerator (4) (trade name: Noccela TS, tetramethylthiuram monosulfide, manufactured by Ouchi Shinko Chemical Industry Co., Ltd., abbreviation: TS) Vulcanization accelerator (5) (trade name: ACCEL CZ, N-cyclohexyl-2-benzothiazolyl sulfenamide, manufactured by Kawaguchi Chemical Industry Co., Ltd., abbreviation: Cz) Vulcanization accelerator (6) (trade name: Nocrac MB, 2-mercaptobenzimidazole, manufactured by Ouchi Shinko Chemical Industry Co., Ltd., abbreviation: MB)
[0116] <Filling agent> Filler (1) (product name: Nanox #30, calcium carbonate, manufactured by Maruo Calcium Co., Ltd., abbreviation: #30) Filler (2) (Thermax Flowform N990, manufactured by CanCab, abbreviation: MT)
[0117] <Resin particles> PE particles (product name: Mipelon XM-221U, polyethylene resin, average particle size 25 μm, manufactured by Mitsui Chemicals, Inc., abbreviation: PE)
[0118] <Impregnated Materials> <monomer> Acrylic monomer 1 (product name: EBECRYL145, PO-modified neopentyl glycol diacrylate, manufactured by Daicel-Allnex Corporation, abbreviation: Acrylic 1) Acrylic monomer 2 (product name: A-TMPT, trimethylolpropane triacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd., abbreviation: Acrylic 2) Acrylic monomer 3 (product name: PETIA, pentaerythritol (tri / tetra) acrylate, manufactured by Daicel Allnex Co., Ltd., abbreviation: Acrylic 3) Vinyl ether monomer (product name: CHDVE, cyclohexanedimethanol divinyl ether, Nippon Carbide Industries Co., Ltd., abbreviation: vinyl ether) Glycidyl ether monomer (product name: Denacol EX-252, hydrogenated bisphenol A diglycidyl ether, manufactured by Nagase ChemteX Corporation, abbreviated name: epoxide) Isocyanate monomer (product name: Millionate MR-100, polymeric polyphenylene polyisocyanate, manufactured by Tosoh Corporation, abbreviated name: Isocyanate) Here, pentaerythritol (tri / tetra)acrylate refers to a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate.
[0119] <Photopolymerization initiator> Photoradical polymerization initiator (trade name: Omnirad 127, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methylpropan-1-one, manufactured by IGM Resins BV, abbreviation: Radical) Photocationic polymerization initiator (trade name: ADEKA Arcles SP150, sulfonium salt-based photocationic polymerization initiator, manufactured by ADEKA Corporation, abbreviation: Cation)
[0120] <Example 1> <Preparation of conductive member 1> [1-1. Preparation of domain-forming rubber composition (CMB)] A rubber composition for domain formation (CMB) was obtained by mixing the materials of the types and amounts shown in Table 2 in a pressure kneader. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 18 minutes. [Table 2]
[0121] [1-2. Preparation of matrix-forming rubber composition (MRC)] A matrix-forming rubber composition (MRC) was obtained by mixing the materials of the types and amounts shown in Table 3 in a pressure kneader. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 18 minutes. [Table 3]
[0122] [1-3. Preparation of rubber composition 1 for forming conductive layer] The materials of the types and amounts shown in Table 4 were mixed with an open roll to prepare rubber composition 1 for forming a conductive member. An open roll with a roll diameter of 12 inches was used as the mixer. The mixing conditions were a front roll rotation speed of 10 rpm, a rear roll rotation speed of 8 rpm, a roll gap of 2 mm, and a total of 20 left and right turns, followed by 10 thin passes with a roll gap of 1.0 mm. [Table 4]
[0123] [1-4. Forming of conductive elastic roller 1] A round bar with a total length of 244 mm and an outer diameter of 6 mm was prepared, the surface of which was made of free-cutting steel and electroless nickel plating was applied. Next, an adhesive (product name: Metalock U-20, manufactured by Toyo Kagaku Kenkyusho) was applied using a roll coater over the entire circumference of the round bar, excluding 11 mm at each end, over a range of 222 mm, to prepare a support.
[0124] Next, a die with an inner diameter of 12.5 mm was attached to the tip of a crosshead extruder having a support feeding mechanism and an unvulcanized rubber roller discharge mechanism, and the temperature of the extruder and crosshead was adjusted to 100° C., and the conveying speed of the conductive support was adjusted to 60 mm / sec. Under these conditions, the conductive member-forming rubber composition was fed from the extruder, and the outer periphery of the support was coated with the conductive member-forming rubber composition in the crosshead, to obtain an unvulcanized rubber roller. Next, the unvulcanized rubber roller was placed in a hot air vulcanizing furnace at 160°C and heated for 60 minutes to vulcanize the layer of the unvulcanized rubber composition, thereby obtaining a roller having a conductive resin layer formed on the outer periphery of the conductive support. After that, 10 mm of each end of the conductive resin layer was cut off, so that the longitudinal length of the conductive resin layer was 224 mm. The surface of the conductive resin layer was then ground with a rotary grindstone to produce a conductive elastic roller 1 having a diameter of 8.44 mm at positions 90 mm from the center to both ends and a central diameter of 8.5 mm.
[0125] [1-5. Preparation of impregnating paint 1 and production of conductive member 1] The materials shown in Table 5 were mixed and dissolved in the amounts shown in Table 5 to prepare impregnation paint 1. Conductive elastic roller 1 was immersed in this impregnation paint 1 for 4 seconds to impregnate it with the acrylic monomer component. It was then air-dried at room temperature for 30 minutes and dried at 90°C for 1 hour to volatilize the solvent. After drying, the conductive elastic roller 1 was rotated and exposed to an accumulated light intensity of 15,000 mJ / cm. 2 The acrylic monomer was cured by irradiating it with ultraviolet light so as to obtain a cured product, and the impregnation process was performed. Note that a high-pressure mercury lamp (product name: handy type UV curing device, manufactured by Mario Network Co., Ltd.) was used as the ultraviolet irradiating device. In this manner, the conductive member 1 according to Example 1 was produced. [Table 5]
[0126] <2. Characterization> [2-1. Impedance measurement] The impedance measurement was carried out by the following measurement method. First, as a pretreatment, a platinum vapor deposition film (electrode) with a thickness of 80 nm was formed on the outer surface of the charging roller, which is a conductive member, while rotating the charging roller. At this time, a masking tape was used to create an electrode with a width of 1.5 cm and uniformity in the circumferential direction. By forming this electrode, it is possible to minimize the contribution of the contact area between the measurement electrode and the conductive member due to the surface roughness of the conductive member. Next, an aluminum sheet was wrapped tightly around the electrode to form the measurement sample shown in Figure 4.
[0127] An impedance measuring device (product name: Solartron 1260 96W, manufactured by Solartron) was connected from the aluminum sheet to the measurement electrode and to the support. The impedance was measured in an environment of temperature 23°C and relative humidity 50%, with an oscillating voltage of 1 Vpp and a frequency of 1.0 Hz, to obtain the absolute value of the impedance.
[0128] The charging roller (length in the longitudinal direction: 224 mm) was divided into 5 equal regions in the longitudinal direction, and measurement electrodes were formed at one point in each region (a total of 5 points), and the above measurements were performed. The arithmetic average of these values was taken as the impedance of the conductive member. The impedance of conductive member 1 is 5.8×10 6 The results are shown in Table 10.
[0129] [2-2. Measurement of the perimeter and envelope perimeter of the domain in the conductive layer, and the number of domains ] The perimeter and envelope perimeter of the domain may be measured as follows. First, a microtome (trade name: Leica EM FCS, manufactured by Leica Microsystems) was used to cut out a slice having a thickness of about 2 μm from the conductive layer of the conductive member at a cutting temperature of −100° C. The slices were cut out from a total of three locations (i.e., L1 / 4, L2 / 4, and L3 / 4) including the center of the conductive layer in the longitudinal direction and two locations of L / 4 from both ends of the conductive layer toward the center, where L is the longitudinal length of the conductive layer of the conductive member 1. The direction in which the slices were cut out was the direction that formed a cross section perpendicular to the longitudinal direction of the conductive layer. The sections were used to perform platinum deposition on the cut surfaces. The cross-sectional image was taken at 5000 times magnification using a microscope (trade name: S-4800, manufactured by Hitachi High-Technologies Corporation). The obtained image was converted to 8-bit grayscale using image analysis software (product name: ImageProPlus, manufactured by Media Cybernetics) to obtain a monochrome image with 256 gradations. Next, the black and white of the image were inverted so that the domains in the monochrome image became white, and a binarization threshold was set for the brightness distribution of the image based on the Otsu's discriminant analysis algorithm, to obtain a binarized image.
[0130] In the binarized image, a 15 μm square area was cut out, and the perimeter and envelope perimeter were calculated using the count function of the image processing software. The A / B value was calculated using the perimeter A and envelope perimeter B calculated for each domain observed in each observation area, and the proportion (number %) of domains with an A / B value of 1.00 to 1.10 among all observed domains was calculated. In addition, the arithmetic mean value of A from all observed domains and the number of domains in the three observation areas were calculated.
[0131] Next, the observation positions of each section are described. When the thickness of the conductive layer is T, 15 μm square observation areas were placed in three locations in the thickness region from the outer surface to a depth of 0.1T to 0.9T or less on each section, and A and B were measured in a total of nine observation areas. The arithmetic mean value of A / B was calculated using the A and B values of these nine locations, and this was defined as A / B. The proportion of domains in which the A / B value of the conductive member 1 was 1.00 to 1.10 was 85%, and the arithmetic mean value of the A / B value was 1.06. The results are shown in Table 10.
[0132] [2-3. Volume resistivity R1 and R2 of the domain exposed on the outer surface of the elastic layer, and elastic Measurement of the volume resistivity ρm of the matrix in the conductive layer The volume resistivities R1 and R2 of the domains exposed to the outer surface of the elastic layer and the volume resistivity of the matrix in the elastic layer may be measured as follows. Specifically, a scanning probe microscope (SPM) (product name: E-sweep, manufactured by Hitachi High-Tech Science Corporation) was used, and current measurements were performed in SIS-AFM mode, taking into consideration the softness of the sample. The SPM cantilever used was SI-DF3-R.
[0133] First, an ultrathin slice having a thickness of 1 μm was cut from a cross section in the thickness direction of the conductive layer including the surface of the conductive member 1 using a microtome (product name: Leica EM FCS, manufactured by Leica Microsystems) at a cutting temperature of −100° C. When cutting the ultrathin slice, the direction of the cross section was perpendicular to the longitudinal direction of the conductive member (i.e., the thickness direction of the conductive layer) in consideration of the direction in which the charge is transported for discharge. Next, the ultrathin slice was placed on a metal plate in an environment of 23°C and 50% relative humidity. The surface vicinity of the slice was observed with the SPM, and the domain exposed on the outer surface of the elastic layer was identified in the phase image. Then, a current value image was obtained by applying 0.5 V for the part other than the conductive particles in the first region of the cross section and the part other than the conductive particles in the second region. Then, the volume resistivity r1 in the first region and the volume resistivity r2 in the second region were calculated from the obtained current value image and the thickness of the slice. The above procedure was carried out for the following locations. That is, the conductive layer of the conductive member 1 (longitudinal length: 224 mm) was divided into 5 equal parts in the longitudinal direction, and further divided into 4 equal parts in the circumferential direction, and 20 slice samples in total were cut out from each region. From each slice sample, measurements were taken for the volume resistivities r1 and r2 at 60 locations each, for three domains exposed on the surface. The arithmetic average values of the volume resistivities r1 and r2 were taken as the volume resistivities R1 and R2. As described above, the first region is a region having a thickness of 0.1×Ld on the side farthest from the support in the cross section of the domain exposed to the outer surface, when the maximum length of the domain exposed to the outer surface in the thickness direction of the conductive layer is Ld, and the second region is a region having a thickness of 0.1×Ld on the side closest to the support in the cross section of the domain exposed to the outer surface.
[0134] The volume resistivity of the matrix in the conductive layer was measured as follows. That is, when the thickness of the conductive layer is T, the volume resistivity was measured in three locations in the matrix portion of the thickness region from the outer surface to a depth of 0.1T to 0.9T of each prepared slice in the same manner as above, for a total of nine locations. The arithmetic average value was taken as the volume resistivity of the matrix.
[0135] The volume resistivity of the domains in the conductive layer was measured as follows: That is, the volume resistivity of the domains was measured in the same manner as in the measurement of the volume resistivity of the matrix, except that the measurement was performed at the locations of the ultrathin slices corresponding to the domains, including the conductive particle portions.
[0136] R1 of conductive material 1 is 3.1×10 9 Ω cm, R2 is 4.2×10 8 The resistivity of the matrix was 9.1×10 13 The results are shown in Tables 10 and 11.
[0137] [2-4. Ratio of the cross-sectional area of the conductive particle contained in the domain to the cross-sectional area of the domain ( S c / S) calculation] The slices with platinum deposition prepared in 2-2 above were photographed at 20,000x magnification using a scanning electron microscope (SEM) (product name: S-4800, manufactured by Hitachi High-Technologies Corporation) to obtain cross-sectional images. Next, image analysis software (product name: ImageProPlus, manufactured by Media Cybernetics) was used to binarize the image so that the carbon black in the domains could be distinguished. Furthermore, an observation area large enough to accommodate one domain was extracted from the obtained binarized image, and the cross-sectional area S of the domain and the cross-sectional area S of the carbon black as a conductive particle contained in the domain were obtained by using a counting function. c And S c The cross-sectional area ratio of the conductive particles in the domain was calculated using / S. Conductive material 1 S c The / S was 28.0 area %. The results are shown in Table 10.
[0138] [2-5. How to confirm interpenetrating polymer network structure (IPN)] The interpenetrating polymer network structure (IPN) can be confirmed, for example, by the following method. From a cross section including the surface of the conductive member 1, an ultrathin section having a thickness of 100 nm was cut out using a microtome (product name: Leica EM FCS, manufactured by Leica Microsystems) at a cutting temperature of -100°C. When cutting out the ultrathin section, the direction of the cross section was set perpendicular to the longitudinal direction of the conductive member, taking into account the direction in which the charge is transported for discharge. The prepared slice was stained using a staining agent, and the domain portion was identified using a transmission electron microscope (product name: H-7100FA, manufactured by Hitachi, Ltd.), and then the first and second regions of the cross section were photographed. Examples of the staining agent include osmium tetroxide, ruthenium tetroxide, and phosphotungstic acid. Similarly, the matrix present at the same depth as the first and second regions from the outer surface of the conductive layer was also photographed. In the case of the conductive member 1, the rubber portion was stained by using osmium tetroxide as a staining agent, and the interpenetrating polymer network structure (IPN) could be confirmed. The rubber portion stained by the reaction of osmium tetroxide with the double bond of the rubber was observed to be black, whereas the curable resin portion constituting the interpenetrating polymer network structure (IPN) was observed to be white, and therefore it was determined to be an interpenetrating polymer network structure. The monomer of the curable resin constituting the interpenetrating polymer network (IPN) was confirmed by taking a slice of the impregnated region in the conductive layer, adding an organic alkaline reagent such as tetramethylammonium hydroxide (TMAH), and using pyrolysis gas chromatography-mass spectrometry (Pyr-GCMS). In the first region of the conductive member 1, an interpenetrating polymer network (IPN) of the curable resin using acrylic 1 as a monomer was confirmed. In the second region, no interpenetrating polymer network was confirmed. The results are shown in Table 11.
[0139] <3. Evaluation as an electrostatic component> The conductive member 1 was used as a charging roller, and the fogging performance under low charging bias conditions was evaluated as follows. A laser printer (product name: HP LaserJet Pro M404, manufactured by Hewlett-Packard Company) was prepared as an electrophotographic image forming apparatus. A conductive member 1 was attached as a charging roller of a process cartridge for this laser printer. The main body of the laser printer was also modified so that any voltage could be applied to the charging roller, developing roller, and intermediate transfer belt from an external power source (product name: Model 615, manufactured by Trek Japan Co., Ltd.). Next, the main body of the laser printer and the process cartridge were left to stand for 48 hours in a high temperature and high humidity environment (HH environment) with a temperature of 30° C. and a relative humidity of 80% in order to acclimate them to the measurement environment. Next, the process cartridge was loaded into the main body of the laser printer. Then, the external power supply was set so that the non-exposed portion (Vd) of the photoconductor of the charging roller was 350 V, the exposed portion (Vl) of the photoconductor was 100 V, and the developing bias was 175 V, and a charging bias of − (minus) 800 V was applied to the charging roller. Then, a white solid image was output under the HH environment. The obtained white solid image was evaluated by the following method. The evaluation result at this time is also called the “initial fogging number”.
[0140] (Method of evaluating fogging) Nine points on the solid white image were observed at 500x magnification with an optical microscope, and the number of black spots caused by toner particles present in an observation area of 1 mm square was counted, and this number was taken as the number of fog spots on the paper. When the conductive member 1 was used as a charging roller, the initial fog was 187. The fog after the durability test was 123%. The results are shown in Table 11. In this embodiment, the initial number of fog particles is preferably 250 or less, particularly preferably 200 or less, and the ratio of the number of fog particles after durability testing to the initial number of fog particles is suppressed to 130% or less, particularly preferably 115% or less, which is used as an indicator of the manifestation of the effects of the disclosure of the present application.
[0141] Next, under the same environment, using the above laser printer, while maintaining the image formation conditions, 10,000 images were formed in which the letter "E" of 4 points was printed so that the coverage rate was 1% of the area of A4 size paper. Then, the conductive member 1 was removed from the process cartridge and incorporated into a new process cartridge as a charging roller. Then, one white solid image was output under the same conditions as the "initial fog number". The fog on the obtained white solid image was observed and evaluated by the following fog evaluation method. The evaluation result at this time is also called the "fog number after durability". The ratio of the fog number after durability to the initial fog number was taken as the fog after durability (%).
[0142] Here, the developer installed in the laser printer is negatively charged. Therefore, when a solid white image is output, the developer does not transfer to the photoconductor or paper. However, as described above, under low charging bias conditions, excessively charged areas may occur on the surface of the photoconductor due to localized strong discharge from the charging member. A small amount of positively charged developer present in the developer transfers to the excessively charged areas of the photoconductor, and as a result, even when a solid white image is formed, black spots originating from the developer are observed, and so-called "reverse fog" occurs on the solid white image. This phenomenon is more likely to occur under low charging bias conditions. The fog after durability also includes fog caused by dirt attached to the surface of the conductive member 1 due to durable use of the conductive member 1.
[0143] <Examples 2 to 23> The CMB was changed to the formulation shown in Table 6, the MRC to the formulation shown in Table 7, the conductive rubber composition to the formulation shown in Table 8, the impregnation paint to the formulation shown in Table 9, and the conductive layer to the formulation shown in Table 10. Conductive members 2 to 23 were produced in the same manner as in Example 1. Then, they were evaluated in the same manner as in Example 1. The results are shown in Tables 10 and 11.
[0144] <Example 24> The CMB was changed to the formulation shown in Table 6, the MRC to the formulation shown in Table 7, the conductive rubber composition to the formulation shown in Table 8, the impregnation paint to the formulation shown in Table 9, and the conductive layer to the formulation shown in Table 10, and the molding method of the conductive elastic roller 24 was changed as follows. Otherwise, the conductive member 24 was produced in the same manner as in Example 1. Then, it was evaluated in the same manner as in Example 1. The results are shown in Tables 10 and 11.
[0145] [1-6. Forming of the conductive elastic roller 24] A round bar with a total length of 244 mm and an outer diameter of 6 mm was prepared, the surface of which was made of free-cutting steel and electroless nickel plating was applied. Next, an adhesive (product name: Metalock U-20, manufactured by Toyo Kagaku Kenkyusho) was applied using a roll coater over the entire circumference of the round bar, excluding 11 mm at each end, over a range of 222 mm, to prepare a support.
[0146] Next, a crosshead extruder (manufactured by Mitsuba Manufacturing Co., Ltd.) was used to cover the conductive rubber composition 24, and a crown-shaped unvulcanized rubber roller was produced. A die with an inner diameter of 8.5 mm was attached to the tip of the crosshead. The molding temperature of the cylinder, screw, and crosshead was set to 100°C. The conveying speed of the support was conveyed while changing the feed speed to form a crown shape, and was adjusted so that the arithmetic average speed when molding one charging roller was 47 mm / sec. At the die outlet, the conductive rubber flows out at the same speed as the core metal, so the average flow speed when molding one roller is 47 mm / sec, which is the same as the conveying speed of the support. The rotation speed of the screw was adjusted so that the outer diameter of the unvulcanized rubber roller was 8.6 mm at the longitudinal center with respect to the conveying speed of the support. The molded unvulcanized rubber roller had a crown shape, with an outer diameter of 8.5 mm at the longitudinal center and an outer diameter of 8.44 mm at positions +90 mm from the longitudinal center position to both ends. Thereafter, the unvulcanized rubber roller was vulcanized by heating in an electric furnace at a temperature of 160° C. for 60 minutes, and both ends were cut to produce a conductive elastic roller 24 with a length of 224 mm in the axial direction where the conductive rubber was formed.
[0147] <Comparative Examples 1 to 4> Conductive members 25 to 28 were produced in the same manner as in Example 1, except that the CMB was changed to the formulation shown in Table 6, the MRC was changed to the formulation shown in Table 7, the conductive rubber composition was changed to the formulation shown in Table 8, the impregnation paint was changed to the formulation shown in Table 9, and the conductive layer was changed to the formulation shown in Table 10. Then, conductive members 25 to 28 were produced in the same manner as in Example 1. The results are shown in Tables 10 and 11. [Table 6] [Table 7] [Table 8] [Table 9] [Table 10]
[0148] In the table, Sc / S indicates the ratio (area %) of the cross-sectional area of the conductive particle to the cross-sectional area of the domain. [Table 11]
[0149] In the table, the presence or absence of an MD structure indicates the presence or absence of a matrix-domain structure, Y indicates that R1>R2 is satisfied, and N indicates that R1>R2 is not satisfied.
[0150] The present disclosure relates to the following configurations. (Configuration 1) a support having an electrically conductive outer surface; a conductive layer disposed on an outer surface of the support, the conductive layer has a matrix containing a crosslinked product of a first rubber and a plurality of domains dispersed in the matrix, the plurality of domains include a crosslinked product of a second rubber and conductive particles; at least a portion of the plurality of domains are exposed at an exterior surface of the electrophotographic conductive member; the outer surface of the electrophotographic conductive member is composed of the matrix and an exposed portion of the domain exposed on the outer surface of the electrophotographic conductive member, An electrode is provided directly on the outer surface of the electrophotographic conductive member, and an AC voltage having an amplitude of 1 V and a frequency of 1.0 Hz is applied between the outer surface of the support and the electrode in an environment of a temperature of 23° C. and a relative humidity of 50%. The impedance is 1.0×10 3 ~1.0×10 8 Ω, The domain exposed on the outer surface of the electrophotographic conductive member is referred to as domain A, and in a cross section of the conductive layer of domain A in the thickness direction of the conductive layer, The maximum length is Ld. A region having a thickness of 0.1×Ld on the farthest side from the support in the cross section of the domain A is defined as a first region, When a region having a thickness of 0.1×Ld on the side closest to the support in the cross section of the domain A is defined as a second region, a volume resistivity R1 of a portion of the first region that is not the conductive particles and a volume resistivity R2 of a portion of the second region that is not the conductive particles satisfy R1>R2; 1. An electrophotographic conductive member comprising: (Configuration 2) 2. The electrophotographic conductive member according to Configuration 1, wherein the volume resistivity R1 and the volume resistivity R2 satisfy R1 / R2≧3.0. (Configuration 3) The electrophotographic conductive member according to Structure 1 or 2, wherein the domain exposed on the outer surface of the electrophotographic conductive member further contains at least one resin selected from the group consisting of a (meth)acrylic resin, an epoxy resin, a vinyl ether resin, and a urea resin, and the resin constitutes an interpenetrating polymer network structure together with the first rubber and the second rubber. (Configuration 4) The electrophotographic conductive member according to any one of Structures 1 to 3, wherein the first region further contains a (meth)acrylic resin, and the (meth)acrylic resin forms an interpenetrating polymer network structure together with the first rubber and the second rubber, and the second region does not contain a (meth)acrylic resin. (Structure 5) The electrophotographic conductive member according to any one of Configurations 1 to 4, wherein, when a length in the longitudinal direction of the conductive layer is L and a thickness of the conductive layer is T, observation regions of 15 μm square are placed at three locations in a thickness region from an outer surface of the conductive layer to a depth of 0.1T to 0.9T for each of a total of three locations, i.e., a center in the longitudinal direction of the conductive layer and two locations from both ends of the conductive layer toward the center, the length being L / 4, and in each of the nine domains observed in each of the observation regions, the perimeter of the domain is A and the envelope perimeter of the domain is B, and the proportion of domains having an A / B value of 1.00 to 1.10 is 80% or more by number. (Configuration 6) In a domain observed in a cross section in the thickness direction of the conductive layer, the ratio S of the cross-sectional area of the conductive particle to the cross-sectional area of the domain c 6. The electrophotographic conductive member according to any one of configurations 1 to 5, wherein / S is 20.0 to 35.0 area %. (Configuration 7) The volume resistivity ρm of the matrix is 1.0×10 8 ~1.0×10 17 7. The electrophotographic conductive member according to any one of configurations 1 to 6, wherein the resistivity is Ω·cm. (Configuration 8) The first rubber includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM); The second rubber includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM); The electrophotographic conductive member according to any one of Configurations 1 to 7. (Configuration 9) The absolute value of the difference in solubility parameter (SP value) between the first rubber and the second rubber is 0.4 to 5.0 (J / cm 3 ) 0.5 9. The electrophotographic conductive member according to any one of Configurations 1 to 8, wherein: (Configuration 10) The combination of the first rubber and the second rubber is SBR and NBR NBR and SBR NBR and BR EPDM and NBR EPDM and SBR IR and SBR BR and NBR SBR and EPDM, or SBR and IR 10. The electrophotographic conductive member according to claim 9, (Configuration 11) 11. A process cartridge configured to be detachably mountable to a main body of an electrophotographic image forming apparatus, the process cartridge comprising the electrophotographic conductive member according to any one of Configurations 1 to 10. (Configuration 12) 11. An electrophotographic image forming apparatus comprising the electrophotographic conductive member according to any one of Configurations 1 to 10. (Configuration 13) the electrophotographic image forming apparatus comprises an electrophotographic photoreceptor and a charging member for charging the electrophotographic photoreceptor, 13. An electrophotographic image forming apparatus according to embodiment 12, wherein the charging member is the electrophotographic conductive member. (Configuration 14) 14. The electrophotographic image forming apparatus according to claim 13, wherein a charging bias applied between said electrophotographic photosensitive member and said charging member is −700 V or more and −900 V or less.< / epdm> < / sbr> < / nbr>
Claims
1. a support having an electrically conductive outer surface; a conductive layer disposed on an outer surface of the support, the conductive layer has a matrix containing a crosslinked product of a first rubber and a plurality of domains dispersed in the matrix, the plurality of domains include a crosslinked product of a second rubber and conductive particles; at least a portion of the plurality of domains are exposed at an exterior surface of the electrophotographic conductive member; the outer surface of the electrophotographic conductive member is composed of the matrix and an exposed portion of the domain exposed on the outer surface of the electrophotographic conductive member, An electrode is provided directly on the outer surface of the electrophotographic conductive member, and an AC voltage having an amplitude of 1 V and a frequency of 1.0 Hz is applied between the outer surface of the support and the electrode in an environment of a temperature of 23° C. and a relative humidity of 50%. The impedance is 1.0×10 3 ~1.0 x 10 8 Ω, the domain exposed on the outer surface of the electrophotographic conductive member is designated as domain A, and in a cross section of the domain A in the thickness direction of the conductive layer, the maximum length of the domain A in the thickness direction of the conductive layer is designated as Ld, A region having a thickness of 0.1×Ld on the farthest side from the support in the cross section of the domain A is defined as a first region, When a region having a thickness of 0.1×Ld on the side closest to the support in the cross section of the domain A is defined as a second region, a volume resistivity R1 of a portion of the first region that is not the conductive particles and a volume resistivity R2 of a portion of the second region that is not the conductive particles satisfy R1>R2; 1. An electrophotographic conductive member comprising:
2. 2. The electrophotographic conductive member according to claim 1, wherein the volume resistivity R1 and the volume resistivity R2 satisfy R1 / R2 ≥ 3.
0.
3. 2. The electrophotographic conductive member according to claim 1, wherein the domain exposed on the outer surface of the electrophotographic conductive member further contains at least one resin selected from the group consisting of a (meth)acrylic resin, an epoxy resin, a vinyl ether resin and a urea resin, and the resin constitutes an interpenetrating polymer network structure together with the first rubber and the second rubber.
4. 2. The electrophotographic conductive member according to claim 1, wherein the first region further contains a (meth)acrylic resin, the (meth)acrylic resin forms an interpenetrating polymer network structure together with the first rubber and the second rubber, and the second region does not contain a (meth)acrylic resin.
5. 2. The electrophotographic conductive member according to claim 1, wherein, when a length in the longitudinal direction of the conductive layer is L and a thickness of the conductive layer is T, observation regions of 15 μm square are placed at three locations in a thickness region from an outer surface of the conductive layer to a depth of 0.1T to 0.9T for each of a total of three locations, i.e., a center in the longitudinal direction of the conductive layer and two locations at L / 4 from both ends of the conductive layer toward the center, and, in each of the nine observation regions, a perimeter of the domain is A and an envelope perimeter of the domain is B, and a proportion of the number of domains having an A / B value of 1.00 to 1.10 is 80% or more by number.
6. In a domain observed in a cross section in the thickness direction of the conductive layer, the ratio S of the cross-sectional area of the conductive particle to the cross-sectional area of the domain c 2. The electrophotographic conductive member according to claim 1, wherein / S is from 20.0 to 35.0 area %.
7. The volume resistivity ρm of the matrix is 1.0×10 8 ~1.0 x 10 17 2. The electrophotographic conductive member according to claim 1, wherein the resistivity is Ω·cm.
8. The first rubber includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM); The second rubber includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), and ethylene propylene diene rubber (EPDM); 2. The electrophotographic conductive member according to claim 1.
9. The absolute value of the difference in solubility parameter (SP value) between the first rubber and the second rubber is 0.4 to 5.0 (J / cm 3 ) 0.5 2. The electrophotographic conductive member according to claim 1,
10. The combination of the first rubber and the second rubber is SBR and NBR NBR and SBR NBR and BR EPDM and NBR EPDM and SBR IR and SBR BR and NBR SBR and EPDM, or SBR and IR 10. The electrophotographic conductive member according to claim 9, wherein
11. 11. A process cartridge configured to be detachably mountable to a main body of an electrophotographic image forming apparatus, comprising the electrophotographic conductive member according to claim 1.
12. An electrophotographic image forming apparatus comprising the electrophotographic conductive member according to any one of claims 1 to 10.
13. the electrophotographic image forming apparatus comprises an electrophotographic photoreceptor and a charging member for charging the electrophotographic photoreceptor, 13. An electrophotographic imaging apparatus according to claim 12, wherein said charging member is said electrophotographic conductive member.
14. 14. The electrophotographic image forming apparatus according to claim 13, wherein a charging bias applied between said electrophotographic photosensitive member and said charging member is −700 V or more and −900 V or less.
Citation Information
Patent Citations
Conductive member, process cartridge and electro-photographic image formation apparatus
JP2020166209A